2018
DOI: 10.1017/s0033291717001386
|View full text |Cite
|
Sign up to set email alerts
|

Dementia, post-traumatic stress disorder and major depressive disorder: a review of the mental health risk factors for dementia in the military veteran population

Abstract: BackgroundDementia is currently incurable, irreversible and a major cause of disability for the world's older population. The association between mental health difficulties, such as post-traumatic stress disorder (PTSD) and major depressive disorder (MDD), and dementia has a long history within the civilian population. Despite the increased importance of this link within the military veteran population, who suffer a greater propensity of mental health difficulties and consist largely of over 65s, attention is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Additionally, there is suggestion of independent risk factors that may increase risk of dementia. It remains unknown whether PTSD directly or indirectly causes dementia (Rafferty et al 2018). In the United States, understanding the aetiological association between PTSD and risk of dementia has become a priority (Khachaturian & Khachaturian 2014).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, there is suggestion of independent risk factors that may increase risk of dementia. It remains unknown whether PTSD directly or indirectly causes dementia (Rafferty et al 2018). In the United States, understanding the aetiological association between PTSD and risk of dementia has become a priority (Khachaturian & Khachaturian 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, each additional risk factor may have an additive effect on depletion of cognitive reserve (Rafferty et al . ). A few studies have suggested common risk factors for both PTSD and dementia may have a cumulative effect, resulting in increased risk of dementia such as traumatic brain injury, lower intelligence, cardiovascular disorders, less education, hypertension, and diabetes (Barnes et al .…”
Section: Theme 2: Aetiology Underlying the Relationship Between Ptsd mentioning
confidence: 97%
See 3 more Smart Citations